Medical and social aspects of arterial hypertension (One Health & Risk Management, 2021)
Introduction. High blood pressure is considered the disease of the 21st century. Significant progress has been made in understanding the epidemiology, pathophysiology and risks associated with hypertension, lifestyle strategies have been implemented, drug therapies have been optimized. Nonetheless, blood pressure control rates remain low at global, European and national levels. Consequently, arterial hypertension, although preventable, remains the main cause of cardiovascular disease, general morbidity and premature mortality.Prevention of cardiovascular diseases in adults is based on prevention of risk factors. There are three leading strategies for the prevention of cardiovascular diseases: general population prevention, prevention in people at high risk and secondary prevention. All three strategies are necessary and complementary. Correct identification of risks will allow adequate and timely measures for primary, secondary and tertiary prophylaxis.Aim of the study: estimation of the prevalence of key hypertension risk factors in adult population of the Republic of Moldova and identification and assessment of knowledge gaps.Material and methods. This is a descriptive science paper. Primary data collected by qualitative, semi-structured questionnaire. Sample – 396 adults. Sample selection – random. Other sources used: national and international scientific articles, and statistics provided by the National Bureau of Statistics of the Republic of Moldova.Results. The results of the study show that the most important risk factors are obesity – 41%, and stress - 65%. These 2 factors were also most frequently identified by respondents as factors leading to high blood pressure. 95.2% of respondents had measured their blood pressure at least once in their lifetime. Only 10% of individuals surveyed were diagnosed with high blood pressure, this is due to a large number of undiagnosed people. A WHO survey, in 2014, shows that 43.3% of hypertensive people are undiagnosed It is alarming that 24.7% of deaths caused by fatal complications occur at productive ages. These trends can potentially have significant negative consequences on the public health in the Republic of Moldova. The study determined that 89% of respondents would like to know more information about arterial hypertension and 47% are interested in learning about prevention and prophylaxis.Conclusions. Most importantly, it is propagated by obesity and stress - two factors that can be prevented. This study identified that there is a need for increased information on the causes, prevention and prophylaxis of arterial hypertension. This study also suggests increasing awareness of individuals and promoting the monitoring of blood pressure at home as the basis for an early identification all types of hypertension.  High blood pressure affects all age groups. Females are less represented in clinical trials, nonetheless, high blood pressure is an important fetal and maternal risk factor. Therefore, intervention plans must be individualized to include biological age, individual functions, mental and social health status.